Uso de técnicas de modelagem e análise espacial para avaliação do potencial de aplicação de infraestruturas verdes: estudo de caso da bacia hidrográfica do Córrego da Ressaca, Belo Horizonte - MG - Bárbara Roberta Morais (2022)
One of the major problems today is related to the frequent urbanization of urban watersheds, a fact that has caused a great impact on the environment, mainly due to the process of triggering floods. Currently, Belo Horizonte - MG has 80 mapped locations with flood risks. Lowimpact urban design and development alternatives, such as green technologies, are efficient in the urban stormwater management process. Given the above, the process of modeling compensatory techniques has been the object of study in several places around the world. For these reasons, the objective of this research is to evaluate the efficiency of green roofs, permeable pavements, and linear parks as a sustainable and mitigating measure of urban runoff in the Córrego da Ressaca Watershed in Belo Horizonte-MG, Brazil. For this, a hydrological and hydraulic model of the basin was built and simulations were carried out with scenarios that represent green technologies in the management of the Ressaca basin. The simulated scenarios were: the implementation of green roofs; the combination of green roofs and permeable pavements; the construction of linear parks in the drainage channels with an open section; joint use of green roofs, permeable pavements, and linear parks. For the hydrological and hydraulic modeling, the Storm Water Management Model (SWMM) was used. Continuous precipitation events were used, and the manual calibration method, by trial and error, was used to adjust the water level data. The model achieved a satisfactory performance, obtaining a Nash-Sutcliffe coefficient of 0.86 for calibration and 0.75 for validation. Project precipitations with a return time of 2, 10, 20, 50, and 100 with a critical time duration of 60 minutes were analyzed for all scenarios. For the result, it was observed for the green roofs an average reduction of 8.62% in the peak flow and 17.72% in the drained volume. For the scenario combining permeable pavements and green roofs, an average reduction of 10% in peak flow and 20.07% in runoff volume was verified. The creation of linear parks achieved an efficient response with a reduction in peak flow of 20.73% and the volume drained of 1.29%. The combination of all scenarios, with the union of all three green technologies, obtained the best result with an average decrease of 27.35% in peak flow and 21.07% in drained volume. However, the results showed the efficiency of technologies, mainly combined, in the retention of urban rainwater.